2022
DOI: 10.1002/adfm.202208474
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the Electrochemistry of Gas‐Involved Reactions through Theoretical Calculations and Simulations from Microscopic to Macroscopic

Abstract: Nowadays, gas‐involved electrochemical reactions, such as carbon dioxide reduction reaction (CO2RR), nitrogen reduction reaction (NRR), and hydrogen evolution reaction (HER), have gradually become viable solutions to the global environmental pollution and energy crisis. However, their further development is inseparable from the in‐depth understanding of reaction mechanisms, which are incredibly complicated and cannot be satisfied by experiments alone. In this context, theoretical calculations and simulations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 218 publications
(318 reference statements)
0
27
0
Order By: Relevance
“…It can be clearly observed that the conversion rate of nitrate (97.6%), ammonium generation selectivity (95.2%), and Faradaic efficiency (91.4%) of UiO-CuZn are much higher than those of pristine UiO (46.4, 24.2, and 35.8%), CuZn (32.4, 35.2, and 30.6%), and UiO + CuZn electrocatalysts (36.9, 31.3, and 42.6%) (Figure e), respectively, demonstrating the conspicuous NO 3 RR performance over the CuZn-incorporated UiO electrocatalyst. The Faradaic efficiency of ammonia generation is much higher than the reported N 2 reduction to ammonia because of the extremely high kinetic energy barriers that have to be overcome, ,, while the conversion rate of nitrate and the selectivity of ammonia are superior to the state-of-the-art nitrate reduction systems in similar environments (Figure f, detailed comparison in Table S3). , Compared with most nitrate reduction electrocatalysts reported, the as-prepared electrocatalysts can not only completely remove nitrate pollutants from aqueous solutions but also selectively convert nitrate to high-value ammonia.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…It can be clearly observed that the conversion rate of nitrate (97.6%), ammonium generation selectivity (95.2%), and Faradaic efficiency (91.4%) of UiO-CuZn are much higher than those of pristine UiO (46.4, 24.2, and 35.8%), CuZn (32.4, 35.2, and 30.6%), and UiO + CuZn electrocatalysts (36.9, 31.3, and 42.6%) (Figure e), respectively, demonstrating the conspicuous NO 3 RR performance over the CuZn-incorporated UiO electrocatalyst. The Faradaic efficiency of ammonia generation is much higher than the reported N 2 reduction to ammonia because of the extremely high kinetic energy barriers that have to be overcome, ,, while the conversion rate of nitrate and the selectivity of ammonia are superior to the state-of-the-art nitrate reduction systems in similar environments (Figure f, detailed comparison in Table S3). , Compared with most nitrate reduction electrocatalysts reported, the as-prepared electrocatalysts can not only completely remove nitrate pollutants from aqueous solutions but also selectively convert nitrate to high-value ammonia.…”
Section: Resultsmentioning
confidence: 91%
“…It is increasingly critical to remove nitrates from water and subsequently convert them into harmless or, better yet, high-value-added products. Electrocatalytic reduction driven by renewable electricity has emerged as an effective strategy to manage nitrates in water, during which nitrogen oxyanions, hydroxylamine, dinitrogen, and ammonia are the main products. , Particularly, ammonia (NH 3 ) is the cornerstone for agricultural fertilizer and industrial chemical manufacture and also an important energy storage medium and carbon-free energy carrier. Industrial-scale NH 3 production heavily relies on the energy-intensive Haber–Bosch process, which requires harsh operating conditions (including high temperature and pressure) and consumes significant amounts of energy. As an alternative, the electrocatalytic dinitrogen (N 2 ) reduction reaction (NRR) in water under ambient conditions has attracted increasing attention for its safety, low cost, and environmental friendliness. , However, the reaction rate and selectivity are hampered by the extremely stable NN triple bond (941 kJ mol –1 ) in nonpolar N 2 gas. , Ideally, NO 3 – is considered as an attractive nitrogen source because of the relatively low dissociation energy of the NO bond (204 kJ mol –1 ). Simultaneously, it is one of the most widespread water pollutants in the world, which seriously endangers human health and the ecological environment .…”
mentioning
confidence: 99%
“…For a long time, researches about electrocatalytic CO 2 reduction reaction (CO 2 RR) and electrocatalytic N 2 reduction reaction (NRR) have been mainly focused on the exploration of electrocatalysts since they improve the reaction rate, efficiency, and selectivity toward desired products. [16][17][18] A large number of publications show that numerous efforts have been made to design and construct the active sites on the surface of electrocatalysts to enhance the performance of CO 2 RR and NRR, including the regulation of crystal facets, [19][20][21] surface morphology, [22][23][24][25] particle size, [26][27][28] oxidation state, [29,30] and heteroatom doping. [31][32][33] Although these regulation methods have got some obvious advance, they cannot overcome the fatal flaws of overall electrocatalytic processes, including the low solubility of CO 2 and N 2 in electrolyte, and the competitive hydrogen evolution reaction (HER).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative to storage is the purposeful utilization of CO 2 as a feedstock for the synthesis of various value-added chemicals, known as CO 2 capture and utilization (CCU), which may provide more economic benefits for a carbon-neutral economy. , CCU is expected to utilize renewable energy sources and abundant feedstocks to achieve sustainable chemistry processes and stimulate the development of routes and concepts to go beyond fossil fuels. , Although various single-carbon (C 1 ) and multi-carbon (C 2+ ) products can be selectively produced with greatly reduced carbon footprint to date, the scope of CCU is not, however, limited to C/H/O-based reactants, and the synthesis of valuable chemicals beyond simple carbon species can also be realized. For instance, the incorporation of the element nitrogen could achieve C–N bond formation and yield organonitrogen compounds.…”
Section: Introductionmentioning
confidence: 99%